Surgical Repair of Pleuroperitoneal Communication with Continuous Ambulatory Peritoneal Dialysis - Shoji, Fumihiro; Katsura, Masakazu; Haratake, Naoki; Akamine, Takaki; Takamori, Shinkichi; Takada, Kazuki; Toyokawa, Gouji; Okamoto, Tatsuro; Maehara, Yoshihiko (The Thoracic and Cardiovascular Surgeon, 2019)
Background Pleuroperitoneal communication is a serious complication in patients receiving continuous ambulatory peritoneal dialysis. However, few single-institutional reports discuss the details of pleuroperitoneal communication in continuous ambulatory peritoneal dialysis patients regarding the intraoperative findings, postoperative course, and outcomes.Methods We retrospectively reviewed the records of consecutive pleuroperitoneal communication patients who were treated surgically from September 2008 to March 2016.Results All four patients had right-sided hydrothorax. The time from introduction of continuous ambulatory peritoneal dialysis to the diagnosis of hydrothorax ranged from 1 to 12 months (average: 5.5 months). Case 1 and case 4 had bleblike lesions near the center of the diaphragm; case 2 had a small hole located near the cardiophrenic angle, and case 3 had thinning of the diaphragm near the cardiophrenic angle. All lesions except for case 3 were directly closed with absorbable suture and reinforced by fibrin glue and a polyglycolic acid sheet. In case 3, the thinned diaphragm was reinforced using fibrin glue, a sealing sheet, and pericardial fat pad tissue. Continuous ambulatory peritoneal dialysis was reinitiated an average period of 11 days (range: 4–15 days) postoperatively. During postoperative follow-up, there was no recurrence of hydrothorax. Continuous ambulatory peritoneal dialysis was continued for an average of 16.7 months (range: 3–34 months) after surgical treatment.Conclusions Surgical treatment for pleuroperitoneal communication is a safe and acceptable procedure and could greatly benefit continuous ambulatory peritoneal dialysis patients.
Keywords: pleuroperitoneal communication; continuous ambulatory peritoneal dialysis; surgical treatment; outcome; diaphragm